Marketing Analysis Strategy Organic Rice at UD. Padi Marketing Region Bekasi with Single Agent (Yasin Holistic Super Organic) - Euis Dasipah; Is Zunaini Nursinah; Taryadi Taryadi (UIN Sunan Gunung Djati Bandung, 2013)
Organic food (organic rice) actually is not something new for Indonesian people. Before